2006
DOI: 10.1108/01437720610713521
|View full text |Cite
|
Sign up to set email alerts
|

Public service motivation and organizational citizenship behavior in Korea

Abstract: PurposeThe main theme is to investigate whether the distinct classes of organizational citizenship behavior (OCB) such as altruism and generalized compliance are shown in the Korean context, and whether public service motivation, job satisfaction and organizational commitment are predictors of OCB in Korean civil servants.Design/methodology/approachStructural equation modeling (SEM) is applied to survey data of 1,584 civil servants in Korea to examine the relationships between the three predictors and the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
253
2
30

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(300 citation statements)
references
References 52 publications
15
253
2
30
Order By: Relevance
“…Kim (2006) found that the Organizational Citizenship Behavior is not positively and directly affected by job satisfaction where as Tang (2008) illustrates that the team commitment as a moderating variable positively influences the relationship existing between both organizational citizenship behavior and job satisfactions. Konovsky (1989) (Organ, 1988).…”
Section: Gonza´lez Et Al(2006) Employees Organizationalmentioning
confidence: 99%
“…Kim (2006) found that the Organizational Citizenship Behavior is not positively and directly affected by job satisfaction where as Tang (2008) illustrates that the team commitment as a moderating variable positively influences the relationship existing between both organizational citizenship behavior and job satisfactions. Konovsky (1989) (Organ, 1988).…”
Section: Gonza´lez Et Al(2006) Employees Organizationalmentioning
confidence: 99%
“…As restrições processuais refletem o estado no qual os funcionários estão coagidos pelas regras organizacionais (Buchanan, 1975;Kim, 2006). Os antecedentes das restrições processuais podem influenciar diretamente a satisfação em relação ao cargo dos funcioná-rios.…”
Section: Restrições Processuaisunclassified
“…Isto significa que, em certa medida, o setor público tem incorporado práticas do setor privado. Muitos autores (Roodhooft e Abbeele, 2006;Liu, Tang e Zhu, 2008;Kim, 2006;Brunetto e Farr-Wharton, 2002;Wright e Davis, 2003) descrevem as transformações significativas no setor público, evidenciando o uso de padrões e normas de empreendimentos privados. Essas modificações fizeram com que muitas organizações públicas mudassem a postura com relação a suas metas organizacionais e, para isso, modificaram o contexto e as características do ambiente de trabalho.…”
Section: Introductionunclassified
See 2 more Smart Citations